Women´s judo in Spain. Past and present (Revista de Artes Marciales Asiáticas, 2019)
Women interested in sports have faced up some barriers and prohibitions, in order to participate and become competitors, especially in martial arts and combat sports. Despite this, Spanish female judo has achieved great international success and the female participation in judo is high at all levels. However, their presence in sports media is not equal, taking into consideration the main results and medals obtained by female judokas from Spain. This study aims to show the history of women in judo, particularly in Spain, as well as to highlight their achievements. In addition to offering a description of the female judo coverage in the media and analyzing if there is an unequal treatment depending on the gender in judo. We started with a deep review of the literature about history of female judo, then the incursion and evolution of female judokas were examined and the main results of Spanish judokas since the beginning of women’s competitions were highlighted. Also, we performed a descriptive and an exploratory study to analyze the online press related to sport in Spain.